Maximizing surface reactivity: The impact of electrochemical oxidation as a polydopamine modification step - Uchôa Teixeira, Jean Valdir [UNESP]; Gonçalves Dias, Leonardo Francisco [UNESP]; Brizuela Guerra, Nayrim [UNESP]; Ribeiro Capelin, Guilherme [UNESP]; Roberto Mastelaro, Valmor; Noronha Lisboa-Filho, Paulo [UNESP] (Elsevier, 2025)
Melanin-based materials are highly versatile and widely utilized across various industries, thanks to their customizable surface properties and excellent biocompatibility. Dopamine, a well-studied precursor, has the remarkable ability to self-oxidize and form melanin-like compounds. This molecule can be tailored using cations during the oxidation process or via the chelation of hydroxyl groups in the final material. In order to explore the adaptability of dopamine-based melanin materials, our research focuses on producing particles using an innovative double-step process. The first oxidation is catalyzed by Y3+ in an electrochemical process, followed by further cyclization in a basic medium. We examined the resulting products to gauge the impact of the process on the final molecular arrangement and chelation capacity by utilizing Fe2+ as a cation probe. Surface reactivity was assessed using voltammetry techniques and electrochemical impedance spectroscopy. The results clearly indicate significant improvements in the molecular arrangement, demonstrating that the double-step process delivers higher material stability and superior surface reactivity compared to the conventional alkali self-oxidation method.
Keywords: Dopamine; Electrochemical oxidation; Molecular arrangement; Surface reactivity